Formulation, Optimization And Characterization Of Hydroquinone And Tretinoin-Loaded Polymeric Nanoparticle Gel For Topical Drug Delivery - Sharma, Adarsh; Rathore, Priyanka; Goswami, Neelima; Jain, Nilesh; Goswami, R.B (Journal of Neonatal Surgery, 2025)
The aim of this study was to develop and optimize polymeric nanoparticle (PNP) formulations and gel systems for the controlled and sustained delivery of hydroquinone (HYQ) and tretinoin (TRE). The nanoparticle formulations were prepared using the solvent evaporation method, where Eudragit RS 100 served as the encapsulating polymer, and polyvinyl alcohol (PVA) acted as a stabilizer. Design of Experiment (DOE) software (Design Expert Version 12.0.1.0) was used to optimize the formulation variables, including the polymer concentration, surfactant concentration, and stirring time. A total of 12 formulations were prepared with varying parameters, and particle size, entrapment efficiency (EE), and stability were evaluated. The optimized formulation, NG1, exhibited a particle size of 146.08 nm (predicted: 144.19 nm) and an entrapment efficiency of 86.77% (predicted: 88.15%). The zeta potential was -22.9 mV, indicating good stability of the nanoparticles. In-vitro drug release studies revealed that NG1 provided sustained release, with 96.13% of the drug released at 16 hours. The release kinetics of NG1 were best described by Higuchi's model (R² = 0.9961), confirming that the drug release followed a diffusion-controlled mechanism. In the stability study conducted over 3 months at 25°C, NG1 maintained a clear appearance and showed minimal changes in drug content, with hydroquinone (HYQ) and tretinoin (TRE) retaining 94.85% and 93.67% of their initial content, respectively. The pH increased slightly from 5.1 ± 0.03 to 5.5 ± 0.05, and viscosity decreased from 5628 ± 0.53 cps to 5025 ± 0.12 cps. These results demonstrate that NG1 is a stable and effective formulation for controlled drug delivery. Additionally, six gel formulations (NG1–NG6) were prepared and characterized for their physical properties, including appearance, pH, viscosity, extrudability, and spreadability. NG1 was selected as the optimized gel formulation based on its favorable characteristics, such as a pH of 5.1 ± 0.03, viscosity of 5628 ± 0.53 cps, and excellent extrudability (+++). The gel showed a high drug content retention of 99.81% for HYQ and 98.26% for TRE at baseline. The study demonstrated that NG1 nanoparticles and the associated gel formulation offer a promising approach for the transdermal delivery of hydroquinone and tretinoin, with sustained drug release, good stability, and favorable drug permeation characteristics.